Preventive Maintenance Analysis to Improve the Readiness of Heavy Equipment Hydraulic Excavator Liebherr R9250 & R9350 with Six Sigma Method at PT. XYZ - Putri, Icha Ayu Azzara; Sitania, Farida Djumiati; Sukmono, Yudi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. XYZ is a company in the field of coal mining. The mining production process is carried out by open pit mining, meaning open mining. One of the activities carried out in the production process at PT. XYZ is overburden removal. The excavator used for overburden removal consists of 2 types Liebherr R9250 and R9350. Based on an initial survey, a breakdown occurred on the Liebherr R9250 excavator engine, experiencing a lubrication system failure, and the R9350 experienced a cooling system failure, so the engine was stuck. The purpose of this research is to overcome the problem of unscheduled unit breakdowns on Liebherr R9250 and R9350 hydraulic excavators at the coal mine project PT. XYZ using the Six Sigma method by formulating Define, Measure, Analyze, Improve, Control (DMAIC) that occurs. The results showed that the R9250 and R9350 excavators at the Six Sigma achievement level were in the 1-Sigma category or at the lowest level, with a very uncompetitive description of the quality of the unit's readiness during the production process. This shows that better improvement is needed to support the quality of unit readiness. Based on this research, the recommendations that can be given are that the company needs to improve human resources, monitor spare parts stock, implement maintenance methods, and improve the quality of unit readiness, operation of tools, customizing spare parts specifications, and provision of company facilities.